Functional architecture of low-frequency variants highlights strength of negative selection across coding and noncoding annotations - Gazal, Steven (Nat Genet, 2018)
Common variant heritability has been widely reported to be concentrated in variants within cell-type-specific noncoding functional annotations, but little is known about low-frequency variant functional architectures. We partitioned the heritability of both low-frequency (0.5%≤MAF<5%) and common (MAF≥5%) variants in 40 UK Biobank traits across a broad set of functional annotations. We determined that non-synonymous coding variants explain 17±1% of low-frequency variant heritability ([Formula: see text] ) versus 2.1±0.2% of common variant heritability ([Formula: see text] ). Cell-type-specific noncoding annotations that were significantly enriched for [Formula: see text] of corresponding traits were similarly enriched for [Formula: see text] for most traits, but more enriched for brain-related annotations and traits. For example, H3K4me3 marks in brain dorsolateral prefrontal cortex explain 57±12% of [Formula: see text] vs. 12±2% of [Formula: see text] for neuroticism. Forward simulations confirmed that low-frequency variant enrichment depends on the mean selection coefficient of causal variants in the annotation, and can be used to predict effect size variance of causal rare variants (MAF<0.5%).